POLITICAL IDENTITY AND VIOLENCE: THE CASE OF BOSNIAN WAR - Eriza Putri Tarita; Aviesta Mayvi Syahara Anshori; Virda Rahma Triana Zahra (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
Political identity, once exploited through extreme nationalism and ethnic division, can escalate into violence and armed conflict, as demonstrated by the Bosnian War (1992–1995). The ethnic cleansing carried out by Bosnian Serb forces against Bosnian Muslims was driven by identity politics, as Serbian nationalist elites pursued an ethnically homogeneous territory following the dissolution of Yugoslavia. This case illustrates how ethnicity and religion can be instrumentalised to justify mass atrocity. The Dayton Agreement of 1995 ended the fighting but institutionalised power-sharing along ethnic lines, a structure that continues to hinder the formation of a cohesive national identity and that has produced political marginalisation for minority groups. A more inclusive framework is required to accommodate ethnic diversity while building a unified national identity. This article examines political identity and violence during the Bosnian War using identity politics theory and ethnic nationalism theory as its analytical framework. The study applies a qualitative method through a literature-based (library) research design